2017
DOI: 10.5958/0974-8164.2017.00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Abundance, distribution and diversity of weeds in wheat in Haryana

Abstract: Wheat (Triticum aestivum L.) crop is infested with both grassy and broad-leaf weeds. Losses caused by weeds in wheat vary from 30-50% depending upon type of weed flora, time, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 2 publications
1
15
0
Order By: Relevance
“…which is in quite accordance with previous study. In zero tillage fields there was increase in number of R. retroflex and M. parviflora which is similar to previous reports(Punia et al 2017).…”
supporting
confidence: 91%
“…which is in quite accordance with previous study. In zero tillage fields there was increase in number of R. retroflex and M. parviflora which is similar to previous reports(Punia et al 2017).…”
supporting
confidence: 91%
“…Shakya et al, (2017) recorded that at25 DAS minimum population of weeds (1.33/m 2 ) was registered in pendimethalin 1.0 kg/ha + metribuzin 0.018 kg/ha in wheat crop. Punia et al, (2017) reported that Sulfosulfuron + metsulfuron 32 g ha -1 was recorded less weed density Phalaris minor 3.9 m -2 and broad leaf weed 2.9 m -2 in wheat field. Devi et al, (2018) reported that application of pinoxaden 50 g ha -1 +RM of carfentrazone and metsulfuron @ 25 g ha -1 recorded lowest total weed density in wheat crop.…”
Section: Weed Densitymentioning
confidence: 92%
“…), lambsquarters (Chenopodium album L.), fathen (Chenopodium murale L.), blue pimpernel (Anagallis arrensis L.) and swine cress (Cronopus didymus L.). Punia et al, (2017) The crop weed competition was markedly reduced by weed control treatments as is evident from the significant decrease in weed population, dry matter accumulation, weed killing efficiency, weed control efficiency and weed control index by 6.1%, 41g/m 2 , 38.1%, 67.4%, -23.5% respectively (Singh and Saxena, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However weeds like Cersium arvense and Convolvulus arvensis are also reported as major weed of wheat growing areas of Punjab and Haryana (Gill and Brar, 1975). In Punjab, the weed flora of wheat consists mainly of grassy weeds like Phalaris minor, Avena ludoviciana and broad leaf weeds like Chenopodium album, Cirsium arvense, Medicago denticulataand Convolvulus arvensis (Singh et al, 1993) (Singh et al, 1995). Weed population of wheat field comprises of complex weed flora (Table 1).…”
Section: Weed Flora Associated With Wheatmentioning
confidence: 99%